Essentials of Water Systems Design in the Oil, Gas, and Chemical Processing Industries - Bahadori, Alireza; Clark, Malcolm; Boyd, Bill (SpringerBriefs in Applied Sciences and Technology, 2013)
This text provides valuable insights for decision makers by outlining key technical considerations and requirements of four critical systems in industrial processing plants: water treatment systems, raw water and plant water systems, cooling water distribution and return systems, and fire water distribution and storage facilities. The authors identify the key technical issues and minimum requirements related to the process design and selection of various water supply systems used in the oil, gas, and chemical processing industries.